(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Self-injurious behaviours are amongst the most alarming of all human behaviours and leading cause of death worldwide. The word suicide originated from a latin word Suicidium (to kill oneself). The essential ingredients of suicide include unnatural death with desire from within and reason for ending life. In 2017, Indian Parliament decriminalised suicide. A one-year cross sectional study was conducted from February 2023 to January 2024 in the Department of Forensic Medicine, SPMC, Bikaner. 150 cases with history of suicide subjected to medicolegal autopsy were included in study on a purposive sampling basis. Information was gathered from autopsy related documents, proforma, history of relatives of the deceased, suicide notes, hospital records, concerned investigating agencies and laboratory reports. Number of suicides committed by males were more as compared to females with a ratio of 2:1, maximum in the age group of 21-30 year. Hanging was the most common pattern followed by poisoning. Some cases have previous history of suicide attempt and only few left suicide notes explaining the reason behind their action. Extreme of summer season i.e. months of May, June and July showed more cases and evening time was preferred by most cases. Marital issues were the most common motive behind committing suicide.